2021
DOI: 10.1073/pnas.2025197118
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ marks splenic precursors of multiple nonlymphoid-tissue Treg compartments

Abstract: Foxp3+CD4+ regulatory T cells (Tregs) regulate most types of immune response as well as several processes important for tissue homeostasis, for example, metabolism and repair. Dedicated Treg compartments—with distinct transcriptomes, T cell receptor repertoires, and growth/survival factor dependencies—have been identified in several nonlymphoid tissues. These Tregs are specifically adapted to function and operate in their home tissue—When, where, and how do they take on their specialized characteristics? We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…Similar to Foxp3, PPARγ is also required to drive the specific phenotype of VAT Tregs and their accumulation, the activation of TCRs is a necessary and sufficient condition to induce PPARγ expression ( Cipolletta et al, 2012 ; Li et al, 2018 ). Recent research shows that a PPARγ lo Treg population in the spleen contains precursors of VAT Tregs and produces not only VAT Tregs but also other tissue Tregs, such as liver and skin ( Li et al, 2021 ). The last feature of VAT Tregs is growth factor dependence, especially related to IL-33 and IL-33 receptor ST2 ( Han et al, 2015 ; Kolodin et al, 2015 ).…”
Section: The Phenotypes Factors and Function Of Tissue Tregsmentioning
confidence: 99%
“…Similar to Foxp3, PPARγ is also required to drive the specific phenotype of VAT Tregs and their accumulation, the activation of TCRs is a necessary and sufficient condition to induce PPARγ expression ( Cipolletta et al, 2012 ; Li et al, 2018 ). Recent research shows that a PPARγ lo Treg population in the spleen contains precursors of VAT Tregs and produces not only VAT Tregs but also other tissue Tregs, such as liver and skin ( Li et al, 2021 ). The last feature of VAT Tregs is growth factor dependence, especially related to IL-33 and IL-33 receptor ST2 ( Han et al, 2015 ; Kolodin et al, 2015 ).…”
Section: The Phenotypes Factors and Function Of Tissue Tregsmentioning
confidence: 99%
“…In fact, both GATA3 and PPAR-g are essential for proper Treg cell function in homeostatic conditions (5659). Whereas GATA3 is known to promote Foxp3 stability in inflammatory environments (58), PPAR-g is essential for proper homing of nonlymphoid tissue-localized Treg cells (56). These findings demonstrate that although these transcriptional pathways likely play a role in the stability and location of prorepair Treg cells, their expression is unlikely to define a unique tissue-protective or -reparative Treg cell subset.…”
Section: Searching For a Distinct Prorepair Treg Cell Subsetmentioning
confidence: 91%
“…Evidence suggests that Tregs acquire tissue Treg programming in a gradual, stepwise process that begins in the spleen and lymph nodes and is dependent on BATF ( Hayatsu et al, 2017 ; Miragaia et al, 2019 ; Delacher et al, 2020 ). A Treg population found in the spleen that expresses low levels of the transcription factor, PPARγ, develops into tissue Tregs at multiple sites including skin, VAT, and liver demonstrating that tissue Treg precursors develop in the spleen prior to immigration to their respective tissues ( Li et al, 2021a ).…”
Section: Tissue Tregsmentioning
confidence: 99%
“…Transfer of PPARγlo Tregs led to more efficient seeding of the VAT compared to PPARγ- Tregs, despite being recovered at similar rates in the spleen, supporting the idea that PPARγlo Tregs are likely the progenitors for VAT Tregs ( Li et al, 2018 ). However, a more recent study found that PPARγlo Tregs are the progenitors for Tregs in several non-lymphoid tissues other than VAT, including the liver and skin ( Li et al, 2021a ). It is unclear if Tregs seeding all tissues go through this PPARγlo intermediate.…”
Section: Tissue Tregsmentioning
confidence: 99%
See 1 more Smart Citation